Clinical‐based oral rehabilitation programme improved the oral diadochokinesis and swallowing function of older patients with dementia: A randomised controlled trial - Chen, Ming‐An; Liu, Ching‐Kuan; Yang, Yuan‐Han; Huang, Shun‐Te; Yen, Cheng‐Wei; Kabasawa, Yuji; Huang, Hsiao‐Ling (Journal of oral rehabilitation, 2022)
Objective To evaluate the effectiveness of a clinical‐based oral function intervention on oral function and care behaviours in older patients with mild dementia. Method Participants were randomly assigned to the experimental group (EG) and control group (CG). Both groups received a leaflet on oral health‐related knowledge, and the EG also received an oral function intervention, which was a brief one‐on‐one lesson concerning oral exercise and preventive oral care. Oral exercise included turning the head, pouting lips, bulging cheeks, stretching tongue, articulation exercise and salivary gland massages. A reminder phone call was made every 2 weeks. Perceived xerostomia and dysphagia, plaque index (PI), Winkel tongue‐coating index (WTCI), repetitive saliva‐swallowing test (RSST), oral diadochokinesis (DDK) and oral care behaviours were recorded at baseline and at 3‐month follow‐up. Generalised Estimating Equations (GEE) were used to analyse the indicated effects. Results The EG (n = 59) exhibited greater improvement to the CG (n = 55) in RSST [β = 0.7; effect size (ES) = 0.45], the syllables /pa/ (β = 3.1; ES = 0.37) and /ka/ (β = 2.7; ES = 0.40) in oral DDK, PI (β = −0.2; ES = 0.52) and WTCI (β = −0.8; ES = 0.38). Moreover, the EG exhibited better preventive behaviours in regular dental visits [adjusted odds ratio (aOR) = 2.2], daily mouth cleaning frequency (aOR = 1.6) and mouth cleaning before sleep (aOR = 1.3). Conclusion The brief clinical‐based intervention was effective in improving the swallowing function, oral DDK and plaque control of older patients with mild dementia at 3‐month follow‐up. Mild dementia patients received a clinical‐based oral rehabilitation programme (i.e. oral exercise and oral hygiene care) can improve their dental plaque cotrol, swallowing and oral diadochokinesis function.